2018
DOI: 10.1002/asi.24078
|View full text |Cite
|
Sign up to set email alerts
|

The “Had Mores”: Exploring korean immigrants’ information behavior and ICT usage when settling in the United States

Abstract: The process of settling in a new country can be extremely challenging, entailing various information needs to cope with rapid changes and adjustments to a new environment. Through interviews with 16 Korean immigrants in the United States, we explored their information behaviors in the settlement process. In line with prior work (Shoham & Strauss, 2008), we found that Korean immigrants needed various types of information: housing, work, banking, transportation, law, school, health, and language. Out of these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Employment, housing, language learning and health are prioritised in early transitioning and settling in, followed by making connections in a host country and maintaining connections in the home country. These needs are confirmed by research on various cultural groups of immigrants in the contexts of everyday life and work (for example, Adkins and Moulaison Sandy, 2020; Suh and Hsieh, 2019; Bronstein, 2017; Yoon and Chung, 2017; Shankar et al , 2016; Sibal and Foo, 2016). There is an order to the needs encountered during integration as demonstrated by the information needs matrix developed by Oduntan and Ruthven (2019).…”
Section: Previous Researchmentioning
confidence: 81%
“…Employment, housing, language learning and health are prioritised in early transitioning and settling in, followed by making connections in a host country and maintaining connections in the home country. These needs are confirmed by research on various cultural groups of immigrants in the contexts of everyday life and work (for example, Adkins and Moulaison Sandy, 2020; Suh and Hsieh, 2019; Bronstein, 2017; Yoon and Chung, 2017; Shankar et al , 2016; Sibal and Foo, 2016). There is an order to the needs encountered during integration as demonstrated by the information needs matrix developed by Oduntan and Ruthven (2019).…”
Section: Previous Researchmentioning
confidence: 81%
“…For example, Xie (2000) investigated shifts in information interaction intentions when finding information, McKay, Chang, Smith, and Buchanan (2019) examined browsing behavior in physical libraries to inform the design of digital information environments and McCay‐Peet and Toms (2015) examined serendipity in the context of information acquisition. Other work in this special issue informs design by examining or comparing the information behavior and practices of specific groups, such as Korean immigrants in the United States (Suh & Hsieh, 2019), LGBTQ+ millennials (Kitzie, 2019), visually impaired and sighted people (Sahib, Tombros, & Stockman, 2012), and domain experts and novices (Liu & Zhang, 2019).…”
Section: Embracing the Recent Past And Present: Jasist Research From mentioning
confidence: 99%
“…In the “had mores”: Exploring Korean immigrants' information behavior and ICT usage when settling in the United States , Suh and Hsieh (2019) interviewed 16 recent Korean immigrants to the United States to understand their settlement‐related information behaviors. The immigrants used digital information environments to create a local identity and maintain a global identity.…”
Section: Embracing the Recent Past And Present: Jasist Research From mentioning
confidence: 99%
“…Scholars in a variety of countries have studied immigration technology. For example, in a study of Korean settlement and information behavior, Suh and Hsieh (2019) found that different information needs of Korean immigrants are intertwined; however, health and legal information were vital. Focusing on social media, Information Science researchers have studied its impact on intercultural adaptation (Sawyer and Chen, 2012).…”
Section: Immigrants' Use Of Icts and Social Mediamentioning
confidence: 99%